Penerapan Metode Peer Teaching dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Silam di Sekolah Menengah Atas - Yogi Permana; Nuruddin Araniri; Nurhidayat Nurhidayat (Eduprof : Islamic Education Journal, 2020)
Based on the preliminary research, students there still lack motivation and awareness of the importance of knowledge in the learning process, this is what encourages researchers to raise the formulation of research problems. The formulation of the problem in this study is how to apply the peer teaching method to increase student learning motivation in Islamic Education subjects and what are the supporting and inhibiting factors in how to increase student learning motivation by applying the Peer Teaching method to Islamic Education subjects at SMAN 2 Majalengka. This research uses a descriptive qualitative approach. Data collection techniques used in this study are observation, interviews, and documentation. With research subjects, students and educators at SMAN 2 Majalengka. The results of this study indicate that one of the supporting factors of student learning motivation is the role of the teacher which reflects its nature as a professional educator and one of the inhibiting factors is the role of the teacher that does not reflect his personality as an educator, ignoring the complaints experienced by students in the process. learning, while the results of the application of the peer teaching method of trained students are able to build solidarity with fellow students, instill a caring attitude towards fellow students, create an attitude of mutual acquaintance with fellow students, provide exemplary outside of class hours, respect the ability of students to catch them. other, building an anti-discrimination attitude towards the differences in the abilities of other students, creating an active learning atmosphere and teaching staff is not bored. Absrak Berdasarkan penelitian pendahuluan peserta didik di sana masih kurang memiliki motivasi dan kesadaran akan pentingnya ilmu dalam proses pembelajaran hal inilah yang mendorong peneliti untuk mengangkat rumusan masalah penelitian. Adapun rumusan masalah dalam penelitian ini yaitu Bagaimana cara menerapkan metode peer teaching dalam meningkatkan motivasi belajar siswa pada mata pelajaran PAI dan apa saja faktor pendukung dan faktor penghambat dalam cara meningkatkan motivasi belajar siswa dengan menerapkan metode Peer Teaching pada mata pelajaran PAI di SMAN 2 Majalengka. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data yang di gunakan dalam penelitian ini yaitu observasi, wawancara, dan dokumentasi. Dengan subjek penelitian peserta didik dan tenaga pendidik SMAN 2 Majalengka. Hasil penelitian ini menunjukkan bahwa salah satu faktor pendukung motivasi belajar siswa adalah peran guru yang mencerminkan sifatnya sebagai tenaga pendidik yang profesional dan faktor penghambatnya salah satunya adalah peran guru yang tidak mencerminkan pribadinya sebagai seorang tenaga pendidik, mengabaikan keluh kesah yang di alami peserta didik dalam proses pembelajaran, Sedangkan hasil penerapan dari metode peer teaching peserta didik terlatih untuk dapat membangun solidaritas terhadap sesama peserta didik, menanamkan sikap peduli terhadap sesama peserta didik, mewujudkan sikap saling mengenal antar sesama peserta didik, memberikan keteladanan diluar jam pelajaran, menghargai daya tangkap peserta didik yang lainnya, membangun sikap anti diskriminasi terhadap perbedaan kemampuan peserta didik lainnya, mewujudkan suasana belajar yang aktif dan tenaga pendidik pun tidak jenuh